(untitled) (PJDOL, 2023)
Advent of digital technologies and open learning spaces have superbly influenced higher education worldwide both in the formal and open universities. Open education is emerged as contemporary approach to learning and teaching. Teachers' professional development in open education is a recognized and stimulating research area. MOOCs are innovative way of professional development of university teachers to prepare them via open education. MOOCs are generally provided free to all participants who seekto share their experiences and knowledge for personalized or collaborativelearning. This study was proposed to bring innovation in teacher educationby transforming professional development of university teachers through MOOCs. Followed by the positivist paradigm, the study was descriptive in nature by using quantitative and qualitative research methods. T